2017
DOI: 10.1308/rcsann.2017.0063
|View full text |Cite
|
Sign up to set email alerts
|

Superior mesenteric artery syndrome: a single centre experience of laparoscopic duodenojejunostomy as the operation of choice

Abstract: INTRODUCTION The superior mesenteric artery (SMA) syndrome, or Wilkie's syndrome, is a rare cause of postprandial epigastric pain, vomiting and weight loss caused by compression of the third part of the duodenum as it passes beneath the proximal superior mesenteric artery. The syndrome may be precipitated by sudden weight loss secondary to other pathologies, such as trauma, malignancy or eating disorders. Diagnosis is confirmed by angiography, which reveals a reduced aorto-SMA angle and distance, and contrast … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
26
0
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 16 publications
1
26
0
6
Order By: Relevance
“…Among surgical options to consider are lysis of the ligament of Treitz, gastrojejunostomy, and duodenojejunostomy. Recently, a laparoscopic approach has also been reported [1,2,[23][24][25]. In 1927, Wilkie concluded that duodenojejunostomy was the treatment of choice [26].…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…Among surgical options to consider are lysis of the ligament of Treitz, gastrojejunostomy, and duodenojejunostomy. Recently, a laparoscopic approach has also been reported [1,2,[23][24][25]. In 1927, Wilkie concluded that duodenojejunostomy was the treatment of choice [26].…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…In addition, we agree with other surgeons that asking adolescent patients to have a nasojejunal tube for several weeks is very difficult . Several alternative surgical approaches have been described in the literature: duodenal derotation , laparoscopic duodenojejunostomy , robot‐assisted laparoscopic duodenojejunostomy , Strong's procedure , and laparoscopic Roux‐en‐Y duodenojejunostomy . According to the literature, laparoscopic duodenojejunostomy is the technique of choice for SMA syndrome .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it is rapid, non‐invasive, and minimizes exposure to radiation. Therefore, we believe that ultrasound performed by an experienced pediatric radiologist should be the test of choice .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…En este caso, la paciente presentó inicialmente un síndrome de estenosis gastroduodenal crónico asociado a pérdida de peso progresivo, con anorexia, vómitos biliosos y de alimentos no digeridos de los días previos y que además agregó por el mismo mecanismo fisiopatológico antes descrito, una injuria renal aguda multifactorial con elevación de azoemia y creatininemia, causada por la deshidratación y por compresión de la vena renal izquierda que fue confirmada con ecografía 10,18,21 El objetivo terapéutico en el síndrome de Wilkie es mejorar el estado nutricional, con NPT y dieta enteral por sonda nasoyeyunal (SNY) si es que se logra sortear el obstáculo; de esta manera se genera tejido graso retroperitoneal que ensancha el ángulo mesentérico y alivia la oclusión con muy buenos resultados, descritos en la literatura mayores al 85% 17,22,23 , también se añade la prevención de factores desencadenantes en el campo neuropsíquico. (5) En la paciente se realizó el mismo plan terapéutico a excepción de la colocación de la SNY debido a que la colocación de SNG y el decúbito lateral izquierdo fueron suficientes para aliviar la oclusión en el primer episodio 3,10,24,25 .…”
Section: Discussionunclassified